2009
DOI: 10.1007/s00430-009-0121-x
|View full text |Cite
|
Sign up to set email alerts
|

The clinical value of neutrophil extracellular traps

Abstract: Neutrophil extracellular traps (NETs) have recently been discovered as a central part of antimicrobial innate immunity. In the meanwhile, evidence accumulated that NETs are also generated upon non-infectious stimuli in various clinical settings. In acute or chronic inflammatory disorders aberrantly enhanced NET formation and/or decreased NET degradation seems to correlate with disease outcome. This review summarizes current knowledge about the relation of NETs in a broad spectrum of clinical settings. Specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
96
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(100 citation statements)
references
References 65 publications
(99 reference statements)
2
96
0
2
Order By: Relevance
“…NETs are extracellular chromatin fibers bound to granular, nuclear and cytoplasmic proteins that despite their importance as effective antimicrobial first line defense mechanism, also occur in various clinical settings in the absence of microbial infections and might be associated with pathophysiological conditions (Logters et al, 2009). In a previous study (Naegele et al, 2012), we demonstrated that neutrophils in RRMS patients are more numerous and exhibit a primed state.…”
Section: -Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NETs are extracellular chromatin fibers bound to granular, nuclear and cytoplasmic proteins that despite their importance as effective antimicrobial first line defense mechanism, also occur in various clinical settings in the absence of microbial infections and might be associated with pathophysiological conditions (Logters et al, 2009). In a previous study (Naegele et al, 2012), we demonstrated that neutrophils in RRMS patients are more numerous and exhibit a primed state.…”
Section: -Discussionmentioning
confidence: 99%
“…NETs not only trap and kill pathogens very efficiently but also minimize collateral tissue damage by containing proteases to the DNA fibers and act as physical barriers preventing microbial spread. Despite the well documented importance of NETs as an effective antimicrobial first line defense mechanism, there is increasing evidence that NETs occur in various clinical settings in the absence of microbial infections and that they are probably also associated with pathophysiological conditions (Amulic et al, 2012;Logters et al, 2009). NETosis, the process of neutrophil cell death that leads to expulsion of NETs, can be triggered by different stimuli including pro-inflammatory cytokines such as IL-8 and TNFα, phorbol 12-myristate 13-acetate (PMA) (Brinkmann et al, 2004;Fuchs et al, 2007), activated platelets (Clark et al, 2007) and endothelial cells (Gupta et al, 2010), and placental microparticles (Gupta et al, 2005).…”
Section: -Introductionmentioning
confidence: 99%
“…MCETs are also composed of nuclear histones and the antimicrobial cathelicidin LL37, as well as tryptase, a granular mast cell marker (Supplementary Table 1). 20 Although extracellular trap formation was shown to occur in various clinical conditions (Table 1), 22 it remains unclear whether cell death per se is required for the release of NETs in vivo, as we will discuss below.…”
Section: Release Of Extracellular Trapsmentioning
confidence: 99%
“…It was also reported that NETs in capillary vessels might be related to the pathophysiology of disseminated intravascular coagulation. 19 Although NETs have been extensively studied, [2][3][4][5][6][7][8][9][10] it has been difficult to evaluate NET formation in clinical specimens. The authors have previously reported that purulent sputum from patients with acute respiratory infections contained abundant NETs, the amount of which gradually decreased as the clinical symptoms and inflammation subsided.…”
Section: Introductionmentioning
confidence: 99%